Bioenhancement of Morality, Culture Without Symbols, and Moral Progress - Musiał, Maciej (Sensus Historiae, 2024)
The subject of consideration in this text is the proposal for bioenhancement of morality by Julian Savulescu and Ingmar Persson. After summarizing the key elements of this position, it is interpreted from the perspective of the socioregulatory concept of culture, particularly by highlighting its desymbolizing nature and raising the question of the possibility of conceptualizing it as an expression of moral progress.